ANALISIS KATA SIFAT DARI PARTIZIPIEN DALAM ROMAN „SOWIESO UND ÜBERHAUPT“ KARYA CHRISTINE NÖSTLINGER - Novilia Putri Dwi Ikhwaningdyah; Putrasulung Baginda; Amir Amir (Jurusan Pendidikan Bahasa Jerman FPBS UPI, 2023)
In literary texts, various elements contribute to a writer's ability to convey a specific message or describe a particular situation. One such element is the use of adjectives, and this research focuses specifically on adjectives formed from participles, diverging from the commonplace adjectives encountered in everyday language. To facilitate this investigation, the novel